Wood extracts as unique sources of soluble and insoluble-bound phenolics: reducing power, metal chelation and inhibition of oxidation of human LDL-cholesterol and DNA strand scission - Tasahil Albishi; Joseph H. Banoub; Adriano Costa de Camargo; Fereidoon Shahidi (Journal of Food Bioactives, 2019)
Palm date is an important crop in many Middle Eastern countries. In the present study, seedling date palm wood and old date palm wood were evaluated for their phenolics content. It was found that they may serve as rich source of soluble and insoluble-bound phenolics with promising reducing power and metal chelation. The observed effects were compared with those of oak, quibracho, banana, and pine woods. Syringic acid, (+)-catechin, and (+)-gallocatechin were present in five out of the six tested samples, as evaluated by MALDI-TOF-MS. Therefore, these compounds are good candidates to be monitored by the industry in order to define quality parameters. Additionally, due to their strong ability in counteracting DNA damage caused by peroxyl and hydroxyl radicals (up to 98.42%) and cupric ion-induced human low-density lipoprotein-cholesterol (LDL-c) peroxidation in vitro (up to 95.80%), wood phenolics may render antimutagenic effects and protection against cardiovascular diseases.